Risk Factors for Ulcerative Colitis in Shahrekord, Iran: A Case-Control Study - Hamid Gheibipour; Ghorbanali Rahimian; Ali Ahmadi (Shahrekord University of Medical Sciences, 2019)
Background and aims: Ulcerative colitis (UC) is a chronic inflammatory bowel disease (IBD) which involves the rectum and colonic mucosa, and is often constantly expanding. Few data are available on risk factors in Chaharmahal and Bakhtiari province. Therefore, the aim of this study was to investigate the association between potential risk factors and UC in Shahrekord. Methods: A case-control study was conducted on patients diagnosed with UC. Overall, 27 new cases of UC and 54 healthy controls in the age range of 20-80 years were studied. Participants were recruited from Pathologic Centers in Shahrekord in 2018. Chi-square test and t test and were used. Logistic regression model was employed to analyze the association between risk factors and UC disease. Results: The mean age at diagnosis was 41.74 years (SD: 7.16 years) and 44.94 years (SD: 6.67 years) for case and control subjects, respectively. Moreover, univariate and multiple odds ratio (OR) showed that there was no significant association between UC and any of the risk factors including gender, marital status, education, diastolic blood pressure, history of diabetes, history of hypertension, permanent use of piped water, night shift work, history of thyroid diseases, depression, history of fatty liver disease, history of kidney stones, and sleep time and wake-up time in the morning. Conclusion: Generally, no significant association was observed between UC and the variables in the present study. Thus, further studies with larger sample size are necessary to better understand the other risk factors and environmental determinants of UC.